If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8k + k + -7 + -10k = 0 Reorder the terms: -7 + 8k + k + -10k = 0 Combine like terms: 8k + k = 9k -7 + 9k + -10k = 0 Combine like terms: 9k + -10k = -1k -7 + -1k = 0 Solving -7 + -1k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -1k = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -1k = 0 + 7 -1k = 0 + 7 Combine like terms: 0 + 7 = 7 -1k = 7 Divide each side by '-1'. k = -7 Simplifying k = -7
| 3(2x+4)+6=2(x-5) | | 42m=999 | | 4-3x=26 | | 3x^2+17x+8= | | 42m=9999 | | 1000000+100000000000000000000000000000= | | 3(2x+4)+6=2x-5 | | 180=16r^2 | | 15=-9+x | | 9r^3-36r=0 | | =350-14x | | 20=-5y-3x | | -154x=6-3x | | Y-4y=-60 | | -x=5x-12 | | -24x+9=-3x-4 | | 5x-7x-3=8 | | f(x)=4xsquared-13x+3 | | 3.5-.60+8.3-4.2=t | | 4(m+6)=24+4m | | 2x-11=2x | | 2(-7.5)= | | Q^2=-9 | | 13t^2+5t-8=0 | | 7-3x=2y-9.6x | | w*3=w+24 | | y=4(5x+1)+11 | | 5+-m=13 | | Y+4=-3(x-1) | | X^2-10x=-65 | | -8.6=n-8.1-4.3 | | 4=-x-y |